Bis{(E)-2,4-diiodo-6-[(2-morpholinoethyl)iminomethyl]phenolato}nickel(II) - Xia, Dong-Sheng (International Union of Crystallography, 2008)
In the title mononuclear nickel(II) complex, [Ni(C(13)H(15)I(2)N(2)O(2))(2)], the Ni(II) atom is four-coordinated in a tetrahedral geometry by the imine N and phenolate O atoms of the two Schiff base ligands. The O and N atoms of the morpholine substituent in the ligand are not involved in coordination to the Ni atom.